Influence of Brackish water aquaculture on Soil Salinisation - Mitra Rajarshi; Santra S.C. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Brackish water aquaculture has been debated severely for its environmental consequences. Mushrooming of such farms on reclaimed mangrove lands and converted agricultural land leads to salinisation of agricultural fields of vicinity. In this study around Bhitarkanika National Park of Orissa, significant correlation between aquaculture farming and high soil salinity has been found. The impact was predominant within a distance of 500 m of the aquaculture pond. The villages having higher aquaculture density were also reported to have tendency of high soil salinity, unsuitable especially for production of paddy – the only crop of the region. Considering other environmental conditions the findings strongly suggest that aquaculture farms play predominant roles in soil salinisation.